Assessment of antioxidant and antiproliferative properties of spinach plants grown under low oxygen availability. (26th June 2014) - Fornaciari, Silvia; Milano, Francesco; Mussi, Francesca; Pinto‐Sanchez, Laura; Forti, Luca; Buschini, Annamaria; Arru, Laura
Abstract BACKGROUND In the human diet, the consumption of fresh fruits and vegetables is important in maintaining good health and in preventing chronic diseases. It is known that plant‐derived food is a powerful source of chemopreventive molecules, i.e. antioxidants, and spinach (Spinacia oleracea L., Chenopodiaceae) possesses a wide range of metabolites with such biological activity. Plant stress response could lead to the production of metabolites with high value for human health and this could be a tool to enhance the production of molecules with antioxidant activity in plants. RESULTS Data reported in this paper confirm the antioxidant properties of spinach plants, and show a strong antiproliferative activity of leaf extract on HT‐29 human cell line. Besides, the hypoxic stress seems to affect the pool of antioxidant molecules present in spinach leaves, as verified by means of HPLC‐MS/MS analysis and the aluminium chloride and ABTS assays. CONCLUSION Our findings represent a basis for improving the biological and pharmacological properties of spinach plants, including the use of different growth conditions to modulate the phytocomplex profile of spinach. © 2014 Society of Chemical Industry